Efficacy and safety of intranasal agents for the acute treatment of migraine: a systematic review and network meta-analysis - Guanglu Li; Shaojie Duan; Tiantian Zhu; Zhiying Ren; Hui Xia; Ziyao Wang; Lei Liu; Zunjing Liu (The Journal of Headache and Pain, 2023)
Abstract Background Intranasal agents may be ideal for the treatment of migraine patients. Many new acute intranasal-specific therapies have been developed, but few of them have been directly compared. The aim of this network meta-analysis (NMA) was to compare the efficacy and safety of various intranasal agents for the treatment of acute migraine in adult patients. Methods The Cochrane Register of Controlled Trials, Embase, and PubMed were searched from inception to 15 August 2023. Randomized controlled trials (RCTs) using intranasal agents (no restrictions on dose, formulation, dosing regimen or timing of the first dose) to treat adult patients with acute migraine were included. The primary efficacy endpoint was pain freedom at 2 h, and the primary safety endpoint was adverse events (AEs). The analysis process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results Nineteen studies (21 RCTs, 9738 participants) were included. Compared to the placebo, 5 mg of zolmitriptan using a conventional liquid nasal spray device was the most effective for pain freedom at 2 h [odds ratio (OR): 4.67, 95% confidence interval (CI): 3.43 to 6.43] and 24 h (OR: 5.49, 95% CI: 3.58 to 8.42) among all the interventions. Butorphanol nasal spray 1 mg was the most effective (OR: 8.62, 95% CI: 1.11 to 66.92) for pain freedom at 1 h, but with low-quality evidence. DFN-02 presented the highest freedom from nausea (OR: 4.95, 95% CI: 1.29 to 19.01) and phonophobia (OR: 5.36, 95% CI: 1.67 to 17.22) at 2 h, albeit with lower odds of achieving complete pain freedom. ROX-828 showed the highest improvement in freedom from photophobia at 2 h (OR: 4.03, 95% CI: 1.66 to 9.81). Dihydroergotamine nasal spray was significantly associated with the highest risk of AEs (OR: 9.65, 95% CI: 4.39 to 21.22) and was not recommended for routine use. Zavegepant nasal spray demonstrated the lowest risk of AEs (OR: 2.04, 95% CI: 1.37 to 3.03). The results of sensitivity analyses for the primary endpoints (pain freedom at 2 h and AEs) were generally consistent with those of the base case model. Conclusions Compared with other new intranasal-specific therapies in treating migraine attacks, zolmitriptan nasal spray 5 mg was the most effective agent for pain freedom at 2 h. Zavegepant nasal spray 10 mg had the fewest adverse side effects.